From Meteren to captivity and beyond, surrender and imprisonment of 2 New Zealand entrenching battalion during the First World War : a thesis presented in partial fulfilment of the requirements for the degree Master of Arts in History at Massey University, Manawatū, New Zealand. EMBARGOED until 28th March 2027 - Redpath, Andrew Stuart (Massey University, 2025)
Many Historians have written extensively about the key campaigns involving soldiers of the New Zealand Expeditionary Force. Names such as Passchendaele, Gallipoli and Le Quesnoy have made an indelible importance in the mythic narrative of what is now known as the Anzac spirit. This is a term that has given rise to the notion of comradeship, bravery in the face of adversity and a never-give-in attitude. Historians, however, have largely remained silent on the 210 prisoners of war taken following the Battle of Meteren that took place during the German Spring Offensive of 1918. While Meteren may not meet the criteria of a decisive or strategically significant battle like some of the major engagements of the First World War. It represents a unique piece of New Zealand’s military history. It marked the largest single surrender of New Zealand troops during the war These men due to varying factors, were forced to surrender their position and enter the German Prisoner of War system. This thesis seeks to tell their stories, as members of 2nd New Zealand Entrenching Battalion, before, during and after captivity. It will theorise as to why they are not remembered as well as their comrades in arms.
Embargoed until 28th March 2027.
Keywords: 430320 New Zealand history